One Dose Versus Two Doses of Intravenous Tranexamic Acid in Total Joint Arthroplasty. Issue 11 (1st June 2021) - Golz, Andrew G.; Yee, Heather K.; Davis, Benjamin J.; Adams, William H.; Brown, Nicholas M.
Abstract : Introduction: Despite its widespread use, a single formulation or dosing regimen of tranexamic acid (TXA) has not been universally agreed on for total joint arthroplasty. The purpose of this study is to compare previously uninvestigated single-dose and two-dose regimens in postoperative hemoglobin level and secondary outcomes within 30 days of surgery. Methods: A retrospective search of our institution's database of patients who underwent primary total knee arthroplasty and primary total hip arthroplasty between January 1, 2017, and July 1, 2019, was performed. Patients were divided into two groups: one group received a 1-g bolus of intravenous TXA just before incision and another intravenous 1-g bolus during wound closure, and the second group received a single 1-g intravenous bolus of TXA just before incision. Two doses of TXA were administered in 873 procedures, and a single dose was administered in 647 procedures. Results: A single intravenous TXA dose just before incision was comparable with using two doses of intravenous TXA on patients' postoperative hemoglobin value, length of stay, rate of transfusion, and 30-day postoperative complication rate, although those receiving two doses of TXA trended toward being less likely to require a transfusion (odds ratio = 0.561; 95% confidence interval: 0.296 to 1.062; P = 0.08). A sensitivity analysis was unable to identify a preoperative hemoglobin value that would identify whether patients would benefit from two versus one dose of TXA. Discussion: The use of a single intravenous TXA dose was as efficacious as two doses, without an increase in postoperative complications. Further studies may identify patient subgroups that would benefit from a second dose. Level of Evidence: Level III, retrospective cohort study